REPRESENTASI KULINER NUSANTARA DALAM CERPEN KOMPAS TAHUN 2021 - Arisandi, Isep Bayu (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2024)
This article is based on seven short story titles published in Kompas in 2021 with the limitations of culinary narratives in the stories. The relationship between literature and culinary emphasizes the position of traditional culinary as a cultural trace passed down from generation to generation. Therefore, it is important to study the culinary narratives contained in Indonesian short stories. This article attempts to present a representation of Indonesian culinary delights in short stories published in Kompas in 2021. To answer this problem, Stuart Hall's (1997) representation theory and the reflection representation approach are used. A total of seven short stories studied in this article are entitled